Comparison of the efficacy of two doses of dexmedetomidine as an adjunct to levobupivacaine in infraclavicular brachial plexus block: prospective double-blinded randomized controlled trial - Huda F. Ghazaly; Ahmed Alsaied A. Aly; Zaher Zaki Zaher; Mahmoud M. Hassan; Ahmed Abdelreheem Mahmoud (BMC Anesthesiology, 2022)
Abstract Background This prospective, double-blind, randomized, controlled trial compared the efficacy of two dexmedetomidine doses (50 and 100-μg) combined with levobupivacaine on sensory block duration in infraclavicular brachial plexus block. We hypothesized that perineural dexmedetomidine would extend sensory block duration dose-dependently. Methods The study included 60 patients aged 20 to 60 years of both sex with an ASA I/II undergoing forearm and hand surgery. The patients were randomly assigned into three equal groups (n = 20) for ultrasound-guided infraclavicular brachial plexus block. The L group received 35-mL 0.5% levobupivacaine plus normal saline, the LD50 group received 35-mL 0.5% levobupivacaine plus 50-μg dexmedetomidine, and the LD100 group received 35-mL 0.5% levobupivacaine plus 100-μg dexmedetomidine. Patients were investigated for onset and duration of sensory blockade, time to first postoperative rescue analgesia, and the total 24-h postoperative morphine requirement. Results The LD100 group had a longer sensory block duration (15.55 ± 1.1 h; 95% confidence interval (CI), 15.04–16.06) than the LD50 group (12.8 ± 1.2 h; 95% CI, 12.24–13.36 h) (p < 0.001) or the L group (9.95 ± 1.05 h; 95% CI, 9.46–10.44 h) (p < 0.001). The LD100 group took longer to request postoperative rescue analgesia and required fewer postoperative morphine doses than the LD50 and L groups (P < 0.001). Conclusions Sensory block duration was longer with perineural 100-μg dexmedetomidine as an adjunct to levobupivacaine than with 50-μg dexmedetomidine. Trial registration This study was approved by the Ethics Committee of Aswan University Hospital (approval number: aswu/125/4/17) (date of registration: 04/04/2017). Furthermore, the trial was retrospectively registered at ClinicalTrial.gov (NCT04729868) with a verification date of January 2021.